2006
DOI: 10.3171/spi.2006.5.5.451
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral calcinosis in bilateral facet joints of the lumbar spine in scleroderma

Abstract: ✓Tumoral calcinosis commonly occurs in the articular soft tissues of the extremities but rarely in the spine. The authors performed surgery to treat lumbar tumoral calcinosis in a patient with scleroderma, in whom symptoms of neurological dysfunction had manifested. This 49-year-old woman presented with low-back pain and gait disturbance. Seven years before presentation, scleroderma had been diagnosed, and the patient had received medical treatment ever since. Imaging revealed tumoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…By contrast, spinal calcinosis has been the subject of limited reports,1 2 3 4 5 6 7 and its prevalence and disease–phenotype associations have not been discussed.…”
mentioning
confidence: 99%
“…By contrast, spinal calcinosis has been the subject of limited reports,1 2 3 4 5 6 7 and its prevalence and disease–phenotype associations have not been discussed.…”
mentioning
confidence: 99%
“…Most reports have described that the calcific materials, proven to be hydroxyapatite by pathological analysis 1 , were located at the cervical spine 2-6 and lumbar spine 1,7 . Thoracic spine involvement was demonstrated in only one study 8 .…”
Section: Rheumatologymentioning
confidence: 98%
“…By contrast, spinal calcinosis has been the subject of only limited reports [1][2][3][4][5][6][7][8] . We describe a woman with the diffuse cutaneous form of SSc who presented with serious neurological symptoms, including a rapidly progressive course of motor and sensory disturbance.…”
mentioning
confidence: 98%
“…Tumoral calcinosis involving the lumbar spine is rare; to our knowledge, only 9 studies on lumbar tumoral calcinosis have been reported in the literature (1,2,7,8,9,11,13,14,15). The lesions involved the vertebral bodies, facet joints, dura, and filum terminale (1,2,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The lesions involved the vertebral bodies, facet joints, dura, and filum terminale (1,2,8,9). Scleroderma, systemic sclerosis, and CREST (calcinosis, Raynaud phenomenon, esophageal dysmotility, sclerodactyly, and telangiectasia) syndrome may be the underlying disorders (7,9,12,14).…”
Section: Introductionmentioning
confidence: 99%